PENGARUH PENGUNGKAPAN PERTANGGUNGJAWABAN LINGKUNGAN DAN TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Pradianika, Rima Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of the study is to examine the influence of environmental responsibility and corporate governance on the firm value. The research population is all companies listed in the Indonesia Stock Exchange during 2014-2015, and 24 of which are selected as the samples. The unit of analysis is 48, obtained from the 24 companies meeting the criteria, multiplied with 2-year observation period. The data are analyzed by multiple regression analysis. The result of the study shows that environmental responsibility, institutional ownership, and audit committee influence the firm value; meanwhile, the proportion of independent board of commissioner does not affect the value.Keywords: Environmental responsibility, Institutional ownership, Proportion of independent Board of Commissioner, Audit committee, Firm value.